2011
DOI: 10.1080/00380768.2011.587203
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide emission derived from soil organic matter decomposition from tropical agricultural peat soil in central Kalimantan, Indonesia

Abstract: Our previous research showed large amounts of nitrous oxide (N 2 O) emission (4200 kg N ha À1 year À1 ) from agricultural peat soil. In this study, we investigated the factors influencing relatively large N 2 O fluxes and the source of nitrogen (N) substrate for N 2 O in a tropical peatland in central Kalimantan, Indonesia. Using a static chamber method, N 2 O and carbon dioxide (CO 2 ) fluxes were measured in three conventionally cultivated croplands (conventional), an unplanted and unfertilized bare treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 39 publications
2
41
0
1
Order By: Relevance
“…Based on the calculation method provided by Toma et al [13], the emission factor for N 2 O (EF) was calculated using annual N 2 O emission (kg N ha −1 ·year −1 ) and applied N (kg N ha −1 ·year −1 ) as following equation:…”
Section: Measurement Of Soil Nitrous Oxide and Carbon Dioxide Emissiomentioning
confidence: 99%
“…Based on the calculation method provided by Toma et al [13], the emission factor for N 2 O (EF) was calculated using annual N 2 O emission (kg N ha −1 ·year −1 ) and applied N (kg N ha −1 ·year −1 ) as following equation:…”
Section: Measurement Of Soil Nitrous Oxide and Carbon Dioxide Emissiomentioning
confidence: 99%
“…The thickness of the peat was 2.6-2.8 m. The bulk density and porosity of the surface soil (0-10 cm) were approximately 0.4 g cm −3 and 73-88%, respectively. The C and N contents of the surface soil (0-10 cm) ranged from 530 to 632 and 13 to 14.3 g kg , respectively (Toma et al 2011). The vegetation that existed before the forest fire consisted mostly of deciduous trees, such as Tetramerista glabra Miq., Calophyllum sp., Shorea sp., Combretocarpus rotundatus (Miq.)…”
Section: Field Site Descriptionmentioning
confidence: 99%
“…In studying the characteristics of peat soils, it was found that some agricultural peat soils emit large amounts of nitrous oxide (N 2 O), which is derived from soil organic nitrogen (N) (Toma et al 2011). Although the N 2 O emissions from tropical peatlands tend to be higher and more varied compared with those of other soils, the impacts of land use management on the conversion rate of soil organic N to N 2 O have yet to be clarified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The largest greenhouse gas flux to the atmosphere is CO 2 , which is produced during plant respiration (autotrophic respiration), decomposition (heterotrophic respiration) and rapid oxidation during fires (land cover change). The saturated soils and anaerobic nature of undisturbed (Hadi et al 2005;Novita 2016), but upon agricultural conversion and with use of fertilizers, N 2 O emissions significantly increase (Toma et al 2011;Novita 2016).…”
Section: Measurements Of Greenhouse Gassesmentioning
confidence: 99%